2013
DOI: 10.1002/anie.201306363
|View full text |Cite
|
Sign up to set email alerts
|

Polyhedral Au–Pd Core–Shell Nanocrystals as Highly Spectrally Responsive and Reusable Hydrogen Sensors in Aqueous Solution

Abstract: Absorption signals absorption: The surface plasmon resonance absorption band of tetrahexahedral, octahedral, and cubic Au–Pd core–shell nanocrystals with gold nanocrystal cores was strongly red shifted upon hydrogen absorption into the Pd shell. This reversible spectral shift makes the nanocrystals promising recyclable hydrogen‐gas sensors. Hydrogen absorption could even be detected visually with smaller core–shell octahedra (see picture).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
73
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 80 publications
(75 citation statements)
references
References 27 publications
(3 reference statements)
2
73
0
Order By: Relevance
“…Previously, we have shown that Au−Pd core−shell nanocrystals can act as plasmonic hydrogen sensors by shifting the plasmonic band of the Au cores significantly upon absorption of hydrogen into the lattice of the Pd shell forming PdH. 17,21 Infrared transmission spectra of the Au−Pd supercrystals in a hydrogen environment were recorded (Figure 8b). After filling the sample chamber with hydrogen, the supercrystals exhibit only one resonance at 3.3 μm.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previously, we have shown that Au−Pd core−shell nanocrystals can act as plasmonic hydrogen sensors by shifting the plasmonic band of the Au cores significantly upon absorption of hydrogen into the lattice of the Pd shell forming PdH. 17,21 Infrared transmission spectra of the Au−Pd supercrystals in a hydrogen environment were recorded (Figure 8b). After filling the sample chamber with hydrogen, the supercrystals exhibit only one resonance at 3.3 μm.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…Because hydrogen absorption into the lattice of a Pd shell forming palladium hydride can tune the refractive index of the Pd shell, a pronounced change in the spectral profile in the infrared region has been measured. 17,21,22 These results advance our understanding of supercrystals for their possible optical and electronic applications.…”
Section: ■ Introductionmentioning
confidence: 90%
“…In addition, Pd has a strong affinity toward hydrogen and thus holds a niche position for its purification, storage, and detection [22,85,86]. The reversible hydrogen absorption/desorption on Pd shells of Au-Pd core-shell nanocrystals has been exploited for the development of highly spectrally responsive and reusable hydrogen sensors using gold core as plasmonic antennae [87]. Pd nanocrystals with varying morphologies synthesized by solvothermal synthesis methods are shown in Table 2 [88][89][90][91][92][93][94][95][96].…”
Section: Pdmentioning
confidence: 99%
“…In this context, nanocrystals and nanowires, in particular, are receiving increased attention in fields as diverse as plasmonics, 1,2 catalysis, 3,4 and sensing. 5 Key properties that these nanostructured materials must possess are crystallinity, tunability, and uniformity.…”
Section: ■ Introductionmentioning
confidence: 99%